The Influence of Content Type and Moderation f Event-Based Posting on Instagram Engagement - Tamamudin; Aditya Darmawan (Bapperida Kabupaten Pekalongan, 2025)
This study aims to analyze the influence of content type, content format, and event-based posting on the engagement rate of the Instagram account @banksyariahindonesia. A quantitative approach was applied using content analysis of 200 posts selected through purposive sampling. The dependent variable was engagement rate, while content type and content format served as independent variables, and event-based posting functioned as a moderating variable. Data were analyzed using dummy-based multiple linear regression and moderated regression analysis. The results indicate that promotional content significantly increases engagement rate, whereas content format does not show a significant effect when examined without contextual considerations. Additionally, event-based posting was found to increase engagement rate and moderate the relationship between promotional content and video format with engagement rate. These results indicate that the effectiveness of digital marketing strategies for Islamic banking is driven more by contextual relevance and timing rather than by the structural form of the content itself.